Pattern of Macrovascular Complications and its relationship with HbA1c in Hospitalized Patients with Type 2 Diabetes Mellitus (Journal of Medicine, 2024)
Background: Type 2 diabetes is a common metabolic disorder causing high blood sugar due to insulin resistance and relative insulin deficiency. It poses a significant global health burden, especially in low and middle-income countries. This study explores how well-controlled blood sugar (HbA1c) affects the types and patterns of complications in hospitalized patients with type 2 diabetes. Methods: Conducted over six months at a tertiary care hospital, this cross-sectional study included 200 men and women with T2DM. Data were collected through evaluations and documented. Macrovascular complications were identified using specific criteria: elevated cardiac troponin I for myocardial infarction, neurological deficits with imaging for stroke, and foot ulcers or amputation history for peripheral vascular disease. Results: Macrovascular complications were found in 33% of patients, with myocardial infarction being the most common (48.5%), followed by stroke (37.9%) and peripheral vascular disease (13.6%). Patients with complications had significantly higher HbA1c and blood glucose levels. Conclusion: A significant proportion of hospitalized T2DM patients have macrovascular complications, associated with higher HbA1c levels. These findings emphasize the importance of good glycemic control to prevent such complications.J MEDICINE 2024; 25: 136-140